Inhalational Induction and Maintenance of Sevoflurane-Based Anesthesia or Total Intravenous Anesthesia Using Propofol and Fentanyl in Patients with Concomitant Dyscirculatory Encephalopathy - V. V. Likhvantsev (Obŝaâ Reanimatologiâ, 2013)
Objective: to improve the results of treatment in patients with concomitant cerebrovascular diseases, by reducing the incidence of postoperative delirium due to neuroprotective properties of sevoflurane. Subjects and methods. Eighty2two patients with concomitant dyscirculatory encephalopathy were examined. The goals of the study included evaluating (a) efficiency and safety of total intravenous anesthesia (TIVA) using propofol versus inhalational induction and (b) maintenance of anesthesia (IIMA) using sevoflurane in patients with atherosclerotic and hypertensive encephalopathy undergoing noncardiac surgery. Results. The patients from both groups were susceptible to episodes of unintentional cerebral desaturation (rSO2); however, only the TIVA group showed a high correlation between a decrease in rSO2 and increases in the blood levels of S100beta protein, a marker of neuronal damage, and in the incidence of postoperative delirium (r=0.7321; p=0.0000001) diagnosed in accordance to comprehensive clinical examination and MMSE scores. The IIMA group lacked a relationship of MMSE scores to the episodes of cerebral desaturation (r=0.1609; p=0.4860), which is regarded as a manifestation of the neuroprotective effect resulted from anesthetic preconditioning. Conclusion. sevafluran2based inhalational induction and maintenance of anesthesia in patients with atherosclerotic and hypertensive encephalopathy is preferable over intravenous anesthesia with propofol and fentanyl in patients with concomitatnt disregulatory enc encephalopathy. Key words: cerebral desaturation, postoperative delirium, anesthetic preconditioning, europrotection, sevoflurane.